A Family with Deaf or Hard-of-Hearing Parents and Hearing Children: A Case Study of Two Families - Mikelevičiūtė, Laura; Jakaitė-Bulbukienė, Kristina (Lietuvių kalba, 2024)
The present study analyses the language policy of two families of deaf or hard-of-hearing parents and hearing children. The desire to explore this topic was motivated by the fact that the linguistic situation of families consisting of deaf parents and hearing children is either not explored or the material is inaccessible to those who do not know Lithuanian sign language. A qualitative method of analysis was chosen to collect the material: in-depth semi-structured interviews with both parents individually and observation of joint activities of the whole family. The aspects of the interview analysis were: pre-planning of language policy strategies before the birth of the child and changes as the child grows up, behavior during arguing or in more complicated linguistic situations, i.e. looking at what are the usual compensatory strategies of communication. The analysis of the data shows that families have not developed specific linguistic strategies before having children, but some decisions has been made after the birth of the children, based on the experience of other families in the same situation. However, unlike previous generations, deaf parents have not tried to talk to their hearing children because it is already known that this is not effective. The analysis of the data also shows that both families have not made any special efforts to teach their children either Lithuanian Language or Lithuanian Sign Language. The biggest problem in families is the manipulation of children by their parents’ hearing impairment, and it is also evident that the families in the study deal with this problem differently. When communication difficulties arise, the most common strategies used are cooperative: lip reading, voice pronunciation tactics, use of the alphabet, seeking help from hearing relatives, and the use of paraphrasing strategies. However, the non-cooperative strategies also were mentioned: ignoring, avoiding. This study could be of interest and benefit to researchers working in the field of applied linguistics, families of deaf and hearing people, social workers working with deaf and hearing families and teachers.